Epidemiologia da infecção por Leptospira spp. em áreas rurais nos biomas brasileiros - Silva, Felipe Jorge da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Family farming properties are important places to be considered units of study in the field of Preventive Veterinary Medicine because their environment and handling characteristics of animals typically employed promote the contact between the different species and thus there are greater chances of transmission of infectious agents with zoonotic potential. The objective of this study was to describe epidemiological aspects of the Leptospira spp. infection and of the occurrence of antibodies against Leptospira spp. in humans and animals populations in farms in the Brazilian biomes. Were harvested from free-living wild animals, domestic animals and humans, samples of blood and urine. For serological analysis, the microscopic agglutination test (MAT) was performed. Urine samples were seeded on media Ellighausen, McCullough, Johnson and Harris culture - DifcoR (EMJH) and Fletcher - DifcoR. Samples of which was isolated the bacteria were genotyped, using the technique Multiple Locus Variable number tandem repeat (MLVA), in Leptospirosis Laboratory of the Institute of Pathobiology, Center for Research in Veterinary and Agricultural Sciences, National Institute of Agricultural Technology (INTA), Buenos Aires, Argentina. To determine the risk factors of leptospirosis, a questionnaire was applied to the people of each property. Univariate analysis was performed using the Fisher exact test in order to verify the association of each of the possible risk factors with the dependent variable. Subsequently, was performed a multivariate analysis, which was built a model of logistic regression. In different species, serovars of Leptospira spp. against which antibody titers were found were Icterohaemorrhagiae, Copenhageni, Grippotyphosa, Pomona, Canicola, Wolffi, Hardjo, Panama, tarassovi, Hebdomadis, Shermani, Bratislava, Bataviae, Australis, Castellonis, Andamana, Autumnalis, Pyrogenes, Whiticombi, Javanica and Patoc. There was isolation of ...

Propriedades de agricultura familiar são importantes locais a serem considerados como unidades de estudos na área de medicina veterinária preventiva, pois seu ambiente e as características de manejo dos animais normalmente empregadas favorecem o contato entre as diferentes espécies e, dessa forma, há maiores chances de transmissão de agentes infecciosos com potencial zoonótico. O objetivo do trabalho foi descrever aspectos epidemiológicos da infecção por Leptospira spp. e da ocorrência de anticorpos contra Leptospira spp. em populações humanas e animais em propriedades rurais nos biomas brasileiros. Foram colhidas amostras de sangue e de urina de animais selvagens de vida livre, animais domésticos e de seres humanos. Para o diagnóstico sorológico de leptospirose, foi realizada a prova de soroaglutinação microscópica (SAM). As amostras de urina foram semeadas em meios de cultura Ellighausen, McCullough, Johnson e Harris - DifcoR (EMJH) e Fletcher - DifcoR. As amostras das quais houve isolamento das bactérias foram genotipadas, utilizando a técnica Multiple Locus Variable number tandem repeat (MLVA), no Laboratório de Leptospirose do Instituto de Patobiologia, Centro de Investigação em Ciências Veterinárias e Agronômicas, do Instituto Nacional de Tecnologia Agropecuária (INTA), Buenos Aires, Argentina. Para a determinação dos fatores de risco de leptospirose, foi aplicado um questionário aos indivíduos de cada propriedade. Realizou-se uma análise univariada, utilizando- se o teste exato de Fisher, a fim de verificar a associação de cada um dos possíveis fatores de risco com a variável dependente. Posteriormente foi realizada uma análise multivariada, na qual foi construído um modelo de regressão logística. Nas diferentes espécies, as sorovariedades de Leptospira spp. contra as quais foram encontrados títulos de anticorpos foram Icterohaemorrhagiae, Copenhageni, Grippotyphosa, Pomona, Canicola ...
Keywords: Leptospira; Infecção; Propriedade rural; Epidemiologia; Fatores de risco; Farm ownership